Assessment of Educational Programs Designed to Enhance Students’ Mental and Social Well- Being: A Comprehensive Review” - Vashi, Harshal G. (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: Various programs are implemented internationally to promote the mental and social health of the students in schools. This study systematically reviewed and categorized all resources, indicators, and criteria for evaluating mental and social programs of schools.Materials And Methods: This systematic review was conducted by collecting data from the PubMed, Google Scholar, Scopus, ProQuest, and Web of Science databases using the keywords of “evaluation, mental health program, social health program, behavioural and emotional program.” In the initial review, 4295 studies were found, which reduced to 75 after removing the repetitions and evaluating the studies’ quality. The articles were selected using the PRISMA chart.Results: The findings resulted in three main categories of structure, process, and outcome; 16 subcategories; and 166 codes. The category of structure included the subcategories of human resources, physical space, facilities, training, needed committees and teams, financing, and implementing mental and social programs. The subcategories of process category were functional indicators, guidelines and protocols, communication, documentation, planning/coordination, time management, and monitoring. The subcategories of behavioural‑therapeutic, satisfaction, and educational outcomes were associated with the outcome category.Conclusion: Application of the structure, process, and outcome indicators, derived from the findings of this study, will greatly improve evaluation of the international mental health programs in schools.